The Influence Of Investment Knowledge, Investment Motivation, Financial Literacy, And Capital Market Training On Investment Interest In The Capital Market In The Millennial Generation - Sinaga, Rony Arjuna; Suhartini, Dwi; Widoretno, Astrini Aning (SEAN Institute, 2024)
Students require investment knowledge that will enable them to carry out investment activities. Many students also engage in illegal investments that are not registered with the Financial Services Authority, with the promise of large profits and without risk. Education about investment is obtained from courses such as financial management and investment management. Various aspects are studied in lectures related to investment ranging from returns, decision-making techniques, obstacles, to the risks that investors will face. The type of research employed in this study is quantitative research. The results of research and discussions related to the effect of investment knowledge, investment motivation, financial literacy, and capital market training on investment interest in the capital market in the millennial generation indicate that investment knowledge has a positive effect on investment interest. This implies that when individuals possess in-depth knowledge related to investment, their interest in investing also increases. This is due to the sense of security that is derived from the knowledge of the positive and negative consequences of a given action, which can encourage the individual to take that action. The results of the research indicate that investment motivation has a positive effect on investment interest.